Zespół żyły głównej górnej o obrazie nawracającego obrzęku Quinckego. Opis przypadku - Jolanta Kozłowska-Murawska; Maria Siwicka; Magda Pająk-Grot (Termedia Publishing House, 2011)
Introduction. Superior vena cava syndrome (SVCS) is a complex ofsymptoms of different aetiology, characterized by facial oedema,cyanosis, phlebectasia of the upper half of the chest and glottis oedema.Objective. To present a case of a woman with symptoms and medicalhistory suggesting recurrent Quincke's oedema of drug-induced aetiology,who was finally diagnosed with SVCS due to ongoing pathologyin the mediastinum.Case report. We present a case of a 54-year old woman who twice in thelast year experienced oedema of the face, diagnosed and treated as recurrentQuincke's oedema of drug-induced aetiology. Allergic history waspositive - allergy to grass pollen (hay fever), several episodes of contactallergy. The patient was treated with antihistamines and glucocorticosteroids.Due to the unsatisfactory response to treatment during the secondepisode of oedema, the presence of dilated veins on the chest and theexacerbation of dyspnoea, mainly in the morning, computed tomography(CT) of the chest was performed. The image showed the presence ofpathological masses in the mediastinum and thrombi in the right atrium,the enlarged superior vena cava and the enlarged right jugular vein. Theimage suggested lymphoma and required further differentiation. Basedon the result of CT of the chest, SVCS was diagnosed.Conclusions. The presented case of the patient with face swelling diagnosedas recurrent Quincke's oedema, with seemingly obvious druginductedaetiology, demonstrates the necessity of careful observationof the patient and reported symptoms. It also reflects the diagnostic difficulties,because many conditions may give cutaneous reactions superficiallyresembling angioedema.